Research of Gearbox Shell Vibration and Radiated Noise of Electric Automobile - Gao Chao; Zhao Zhizhuan; Shu Yuanlin; Liu Hai (Jixie chuandong)
Taking a type of transmission as the research object,the axis gear system dynamics model is set up,and the dynamic time history and load spectrum of the transmission shell under the working condition are obtained. Based on dynamic load incentive,the finite element simulation model of the boundary element is established,the vibration acceleration and near sound field radiated noise of the shell surface are calculated. The gearbox shell vibration and radiated noise test platform is built,the shell surface vibration acceleration value and the acoustic noise spectrum of nearly one meter position under the same condition are test,and compared with the simulation results,the validity of the finite element model and the boundary element model is verified. Finally,the different local gearbox shell is optimized,through the simulation calculation,the results show that the optimized gearbox shell vibration amplitude and radiated noise is better inhibition.